The rock of Tanios - Maalouf, Amin. (New York Braziller, 1994)
An exploration of myth, passion and loyalty from the Lebanon's troubled past, The Rock of Tanios is another superbly rich and rewarding novel from the author of Samarkand and Leo the African. Expertly controlling his multi-faceted narrative with prose of great beauty and power, Maalouf delves into the history of an extraordinary life: that of Tanois, child of the mountains.
Keywords: Lebanon--History--1516-1918--Fiction.